A dual‐band wide‐input‐range adaptive cmos rf–dc converter for ambient rf energy harvesting - Heo, Bo Ram; Kwon, Ickjin (Sensors, 2021)
In this paper, a dual‐band wide‐input‐range adaptive radio frequency‐to‐direct current (RF–DC) converter operating in the 0.9 GHz and 2.4 GHz bands is proposed for ambient RF energy harvesting. The proposed dual‐band RF–DC converter adopts a dual‐band impedance‐matching network to harvest RF energy from multiple frequency bands. To solve the problem consisting in the great degradation of the power conversion efficiency (PCE) of a multi‐band rectifier according to the RF input power range because the available RF input power range is different according to the frequency band, the proposed dual‐band RF rectifier adopts an adaptive configuration that changes the operation mode so that the number of stages is optimized. Since the optimum peak PCE can be obtained according to the RF input power, the PCE can be increased over a wide RF input power range of multiple bands. When dual‐band RF input powers of 0.9 GHz and 2.4 GHz were applied, a peak PCE of 67.1% at an input power of −12 dBm and a peak PCE of 62.9% at an input power of −19 dBm were achieved. The input sensitivity to obtain an output voltage of 1 V was −17 dBm, and the RF input power range with a PCE greater than 20% was 21 dB. The proposed design achieved the highest peak PCE and the widest RF input power range compared with previously reported CMOS multi‐band rectifiers.
Keywords: Adaptive; CMOS rectifier; Direct current power; Dual Band; Input power; Power conversion efficiencies; Radio frequency‐to‐direct current power converter; Radiofrequencies; RF energy harvesting; Wide input range; Adaptive; CMOS rectifier; Dual‐band; RF energy harvesting; RF–DC power converter; Wide input range